What Do We See in Images? - Jörgensen, Peter (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper describes preliminary results from two image classification experiments. Ss created their own ad hoc categories in the first. Pre-existing categories were provided in the second. In both of these tasks objects, especially people, were the predominant feature used to categorize the images.